Implementasi Sistem Informasi Manajemen Laboratorium Kebidanan Pada Fakultas Ilmu Kesehatan Universitas Ibrahimy - Muhasshanah Muhasshanah; Siti Qamariyah (Department of Science and Technology Ibrahimy University, 2021)
The Faculty of Health Sciences (FIK) is one of the faculty under the Situbondo Ibrahimy University that develops education in health sector, which in its implementation of the learning process do a lot of practicum both in the laboratory or in the classroom. One of the laboratories is midwifery laboratory. Midwifery laboratory of FIK serves the lending of tools, rooms and packages to students and lecturers, both to be used for the learning process, or to the needs of research and community service. The lending transaction process, with many packages containing a variety of tools, requires an effective and efficient recording data system. The purpose of this research is to help the staffs of midwifery laboratory to serve all the processes of lending, returning, procuring and repairing equipment. This information system provides information about student activity in practicing and using tools in the midwifery laboratory, as well as the availability of tools with student ratios so that they can become decision support for faculty leaders in the procurement and monitoring of tool use in the laboratory.